2016
DOI: 10.1080/13825585.2016.1251549
|View full text |Cite
|
Sign up to set email alerts
|

Purpose in life and cognitive functioning in adulthood

Abstract: With an increasingly aging population, more work is needed to identify factors which may promote the maintenance of normal cognitive functioning. The current study tested the concurrent association between sense of purpose in life and the cognitive variables of episodic memory, executive functioning, and composite cognitive functioning in adults (N = 3489, M = 56.3 years, SD = 12.27, Range = 32-84 years) from the Midlife in the United States study (MIDUS). Correlational analyses suggested that purpose in life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
63
3
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 33 publications
6
63
3
8
Order By: Relevance
“…This finding fits with previous research on purpose in life and cognition. Starting at least as early as middle adulthood, individuals with a higher purpose in life score better on measures of episodic memory and executive functioning, when purpose and cognition are measured concurrently . In older adulthood, purpose in life is associated with less of a decline in tests of memory, perceptual speed, and visual‐spatial ability over a 7‐year follow‐up .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This finding fits with previous research on purpose in life and cognition. Starting at least as early as middle adulthood, individuals with a higher purpose in life score better on measures of episodic memory and executive functioning, when purpose and cognition are measured concurrently . In older adulthood, purpose in life is associated with less of a decline in tests of memory, perceptual speed, and visual‐spatial ability over a 7‐year follow‐up .…”
Section: Discussionmentioning
confidence: 98%
“…Starting at least as early as middle adulthood, individuals with a higher purpose in life score better on measures of episodic memory and executive functioning, when purpose and cognition are measured concurrently. 15 In older adulthood, purpose in life is associated with less of a decline in tests of memory, perceptual speed, and visual-spatial ability over a 7-year follow-up. 16 This protective effect on individual cognitive functions accumulates to lower risk of both mild cognitive impairment and Alzheimer's disease in older adulthood.…”
Section: Statistical Approachmentioning
confidence: 99%
“…The association between PiL, CR, and cognitive function in our subjects has some parallels in the literature. For example, Lewis et al [ 42 ] reported that PiL scores were positively associated with executive functions, memory, and general cognitive performance across the adult lifespan (32-84 years; see also [ 84 ]). Furthermore, McKnight and Kashdan [ 51 ] concluded that a certain degree of abstract capacity, insight, and planning explains interindividual differences in purpose formation, such high-order cognitive processes having also been previously associated with CR estimates [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, PiL has been specifically investigated in the field of cognitive aging and dementia. A higher level of PiL has been associated with better cognitive function in adults without dementia [ 17 ] and in middle-aged individuals [ 42 ]. Moreover, a seminal longitudinal study [ 17 ] found that a high level of PiL predicted a reduced risk for Alzheimer’s disease (AD) or mild cognitive impairment (MCI) after 7 years of follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Using data from these and other studies, NIA-supported researchers have documented a U-shaped age profile of wellbeing in the US population (Stone et al 2010), a positive association between daily experiences of positive affect and longevity (Steptoe and Wardle 2011), and associations between higher levels of purpose in life and reduced risk of mortality (Boyle et al 2009), Alzheimer's disease (Boyle, Buchman, Barnes, & Bennett, 2010), and disability (Boyle, Buchman, & Bennett, 2010), after taking background health and demographic factors into account. The MIDUS study was designed to allow researchers to examine the links between biomarkers of health and dimensions of well-being -particularly its eudaimonic aspects -with emerging findings showing links between subjective wellbeing and emotional recovery to a negative stimulus in the laboratory (Schaefer et al 2013), metabolic syndrome (Boylan and Ryff 2015), cognitive function (Lewis et al 2016), and mortality (Tsenkova et al 2007). Harmonized well-being measures in the HRS and ELSA allowed researchers to examine cross-national differences in the links between educational attainment and subjective well-being in later life (Jivraj and Nazroo 2014).…”
mentioning
confidence: 99%